MENINGKATKAN KEMAMPUAN BERBICARA MELALUI METODE BERCERITA - Ajmah, Ayu Fajarwati, Afifah (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
The problem raised in this study is how to improve speaking ability through storytelling method. Based on the observation in the field, children's speaking ability is still low. The cause of low speaking ability in children is that teachers tend to carry out learning with lectures or assignments. This study aims to improve children's speaking ability at PAUD Izzatuna Pontang District through storytelling method. The type of research used is classroom action research. The data collection techniques used were observation and documentation. Data analysis techniques used descriptive quantitative and qualitative. The results showed that there was an increase in speaking ability in children in group A at PAUD Izzatuna. The steps taken to improve speaking skills are to make apperceptions, the teacher starts storytelling activities, asks questions to children and gives children the opportunity to retell and then reflects on the activities that have been carried out. The improvement can be seen from the observations that have been made, in the pre-action of 33.83%, Cycle I of 53.17% and Cycle II shows that children's speaking ability has increased with the results of very good developing criteria of 90.17%. From the results obtained in the study prove that through the storytelling method can improve children's speaking abi